2020
DOI: 10.1080/15548732.2020.1814541
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following child welfare services: what are they and do they differ for black children?

Abstract: Current calls to end structural racism in the US include proposals to abolish or radically transform child welfare services (CWS). While substantial research finds numerous poor outcomes following maltreatment, the efficacy and acceptability of CWS, particularly for children of color, has long sparked debate. This review summarizes the state of quantitative research across seven domains for children overall and by race with varying degrees of CWS contact. Current research with adequate comparisons provides no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 71 publications
0
48
0
Order By: Relevance
“…In this way, consistent empirical findings can be identified and outcomes for various sub-groups of children-particularly outcomes for different ages and different ethno-racial groups, can be explored. We have written about our understanding of a set of child welfare outcomes, broadly and with special attention to outcomes for Black children, in a separate paper (Barth et al, 2020). The current paper focuses on issues impacting child welfare contact and subsequent service trajectories.…”
Section: Misconceptions To Reconsidermentioning
confidence: 99%
“…In this way, consistent empirical findings can be identified and outcomes for various sub-groups of children-particularly outcomes for different ages and different ethno-racial groups, can be explored. We have written about our understanding of a set of child welfare outcomes, broadly and with special attention to outcomes for Black children, in a separate paper (Barth et al, 2020). The current paper focuses on issues impacting child welfare contact and subsequent service trajectories.…”
Section: Misconceptions To Reconsidermentioning
confidence: 99%
“…Wakefield and Wildeman also suggest that a suite of customized services that were proportionate to family needs might be a better service design than what exists in the U.S. We agree and have also argued-along with others-that we need to address adverse community environments if we are to prevent engagement with child welfare services (e.g., Barth et al, 2020;Drake & Zuravin, 1998;Font & Maguire-Jack, 2015;Garcia & DeNard, 2017;Jones Harden, Simons, Johnson-Motoyama, & Barth, 2020). We agree and have also argued about the import of addressing family needs related to poverty, greater access to evidence-based parenting services, and other supports like adult behavioral health services (Drake, Jonson-Reid, & Dvalishvili, 2022;Garcia, DeNard, Morones, & Eldeeb, 2019;Jones Harden et al, 2020;Libby et al, 2007).…”
Section: Wakefield and Wildeman (2022) Responsementioning
confidence: 84%
“…To the extent that racial disparities in post-reunification environments are larger and/or more favorable for whites than are racial differences in foster home environments, Black-white gaps in incarceration may be larger among youth who reunify versus age out. A recent review identified few studies on racial disparities in the effects of foster care or experiences therein on various developmental outcomes, and of those studies, little indication of especially harmful effects among Black youth (Barth et al 2020). In addition, research on youth who have aged out of care has not found racial differences in educational attainment, employment, or mental health; however, disparities favoring whites were identified in rates of teen fatherhood, homelessness, receiving public assistance, and experiencing poverty (Dworsky et al 2010;Harris et al 2009;Shah et al 2017;Villegas and Pecora 2012).…”
Section: Heterogeneity By Racementioning
confidence: 99%
“…Research suggests that, among youth in foster care, Black youth have higher rates of juvenile justice system involvement than white youth (Cutuli et al 2016). However, it is unclear whether associations between placement or placement characteristics with juvenile incarceration vary by race (Malvaso, Delfabbro, and Day 2016;Barth et al 2020). 3.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%